Challenges and opportunities of passenger data systems (2015)
Looks at the introduction of the passenger information systems from data collected by airlines, its use in various countries and the requirement for those countries wishing to adopt the system to liaise with countries that have gained experience in implementing their procedures.
Keywords: CUSTOMS